2006
DOI: 10.1302/0301-620x.88b3.17273
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical and ultrasonographic findings after Achilles tenotomy in idiopathic club foot

Abstract: Achilles tenotomy is a recognised step in the Ponseti technique for the correction of idiopathic congenital talipes equinovarus in most percutaneous cases. Its use has been limited in part by concern that the subsequent natural history of the tendon is unknown. In a study of 11 tendons in eight infants, eight tendons were shown to be clinically intact and ten had ultrasonographic evidence of continuity three weeks after tenotomy. At six weeks after tenotomy all tendons had both clinical and ultrasonographic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 12 publications
1
34
2
2
Order By: Relevance
“…The final long leg cast is applied after the tenotomy and the foot is positioned in 70°of abduction and only 5°to 10°of dorsiflexion. One ultrasound study suggests the tendon heals within 3 weeks of casting [4].…”
Section: Ponseti Methodsmentioning
confidence: 99%
“…The final long leg cast is applied after the tenotomy and the foot is positioned in 70°of abduction and only 5°to 10°of dorsiflexion. One ultrasound study suggests the tendon heals within 3 weeks of casting [4].…”
Section: Ponseti Methodsmentioning
confidence: 99%
“…123,124 The tendon appears to undergo complete repair within six weeks after the sectioning. 120 Repair of the calcaneal tendon after percutaneous tenotomy in the CC was studied more recently verifying fast healing, with recovery of the mechanical transmission of movements in all the cases three weeks after the sectioning. At six months after sectioning, the repair tissue was similar to the normal tendon.…”
Section: Calcaneal Tendon Sectioningmentioning
confidence: 98%
“…73 Clinical studies with late follow-up showed that tenotomy does not cause late onset effects such as tendon weakening and ruptures. 53,60,113,120,121 Previous studies on other types of disease showed that there is complete repair of the calcaneal tendon after its total sectioning at the myotendineous junction 122 , or more distally. 123,124 The tendon appears to undergo complete repair within six weeks after the sectioning.…”
Section: Calcaneal Tendon Sectioningmentioning
confidence: 99%
“…Ponseti demonstrated correction of most clubfeet in infants using proper manipulative techniques followed by the application of well-moulded long-leg plaster casts and a percutaneous tendo-Achilles tenotomy to correct residual equinus contracture [1]. It is possible access a number of reports published in the literature about this old but recently popularised technique [2][3][4]. In the literature, the indication for tenotomy is reported to be necessary in approximately 70-80% of patients [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is abundant information in the literature describing the Ponseti manipulative and casting technique to correct clubfeet, there are few publications concerning the technique of percutaneous tendo-Achilles tenotomy for residual hindfoot equinus in the clubfoot deformity [1][2][3][4]. Achilles tenotomy should be applied percutaneously and completely, as identified in the original Ponseti technique.…”
Section: Introductionmentioning
confidence: 99%